2001
DOI: 10.1002/cne.1342
|View full text |Cite
|
Sign up to set email alerts
|

Anatomy and physiology of neurons with processes in the accessory medulla of the cockroach Leucophaea maderae

Abstract: The accessory medulla (AMe), a small neuropil in the insect optic lobe, has been proposed to serve a circadian pacemaker function analogous to the role of the suprachiasmatic nucleus in mammals. Building upon considerable knowledge of the circadian system of the cockroach Leucophaea maderae, we investigated the properties of AMe neurons in this insect with intracellular recordings combined with dye injections. Responses of neurons with processes in the AMe to visual stimuli, including stationary white light, m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
72
1
1

Year Published

2002
2002
2012
2012

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 73 publications
(74 citation statements)
references
References 41 publications
0
72
1
1
Order By: Relevance
“…The neurons project via the anterior (two neurons) and posterior (one neuron) optic commissures, innervate the internodular and shell neuropils of the AMe, and send a fan of fibers along the distal surface of the medulla toward the first optic chiasm and lamina. Neurons of this morphological type were found to be unresponsive to light stimuli in intracellular recordings (Loesel and Homberg, 2001). Together with the non-photic phase-response curve obtained by PDF injection, Petri and Stengl (Petri and Stengl, 2002) and Reischig et al (Reischig et al, 2004), therefore concluded that the three PDF-ir VNe transmit phase information to the contralateral pacemaker.…”
Section: Orcokinin-ir Neurons Form a Direct Coupling Pathway Betweenmentioning
confidence: 86%
See 1 more Smart Citation
“…The neurons project via the anterior (two neurons) and posterior (one neuron) optic commissures, innervate the internodular and shell neuropils of the AMe, and send a fan of fibers along the distal surface of the medulla toward the first optic chiasm and lamina. Neurons of this morphological type were found to be unresponsive to light stimuli in intracellular recordings (Loesel and Homberg, 2001). Together with the non-photic phase-response curve obtained by PDF injection, Petri and Stengl (Petri and Stengl, 2002) and Reischig et al (Reischig et al, 2004), therefore concluded that the three PDF-ir VNe transmit phase information to the contralateral pacemaker.…”
Section: Orcokinin-ir Neurons Form a Direct Coupling Pathway Betweenmentioning
confidence: 86%
“…Neural connections between both brain hemispheres of L. maderae serve for bilateral coupling of the clocks and, in addition, for light entrainment of the clock through the contralateral compound eye (Page, 1978;Page, 1981;Page, 1983a). Commissural neurons between both AMae, which might mediate these functions, have been identified (Loesel and Homberg, 2001;Reischig and Stengl, 2002;Reischig et al, 2004). Immunocytochemical studies and injections of neuroactive substances suggest that several neuropeptides and ␄-aminobutyric acid (GABA) play roles as neuromediators in the circadian system of the cockroach (Petri et al, 1995;Petri et al, 2002;Petri and Stengl, 1997;Schneider and Stengl, 2005).…”
mentioning
confidence: 99%
“…Recent findings that both anterior and posterior optic tracts deliver polarization information in the locust S. gregaria (Mappes and Homberg, 2007;Jundi and Homberg, 2010) suggests the possibility that these visual neurons respond to polarized light as well as ordinary visual stimuli in the cockroach, as is demonstrated in a posterior optic tract neuron (Loesel and Homberg, 2001). Future work using controlled visual stimuli (such as color, motion and polarized light stimuli) will be necessary to elucidate the physiological properties of visual input neurons.…”
Section: The Conserved Morphologies Of Theses Two Types Of Neurons Bementioning
confidence: 95%
“…Whether all regularly discharging cells of the cockroach circadian clock are also endogenous circadian pacemaker neurons and vice versa remains to be examined. PDF-IR neurons apparently generate very regular interspike intervals, because intracellular recordings from neurons with the same branching pattern as PDF-IR neurons showed spontaneous discharge rates with regularly spaced spikes (Loesel and Homberg, 2001). In addition, regularly bursting neurons with arborizations in the circadian clock were recorded Homberg, 1998, 2001).…”
Section: Ame Neurons Generate Ultradian Action Potential Oscillationsmentioning
confidence: 99%